Assessment of cataract blindness prevalence and factors associated with surgical coverage in Rwanda - Owusu, Kyei Michael (Division of General Surgery, 2020)
Background: The Rapid Assessment of Avoidable Blindness (RAAB) survey methodology is a cost-effective tool for assessing the burden of blindness and cataract surgical services in a population. This study analyses the 2015 Rwanda National RAAB data to ascertain whether there are gender differences in access to cataract surgical services and also assess whether there is an association between measured distances travelled to access cataract surgical services and the cataract surgical coverage (CSC) in the country. Methods: Secondary data non automated analysis was performed on the 2015 Rwanda RAAB data, which had a sample of 5,275 persons who underwent ophthalmic examinations as per RAAB protocols to elicit the prevalence and causes of blindness and answered a standard questionnaire on barriers to cataract surgery. Cataract blindness prevalence and cataract surgical coverage were estimated for males and females and assessed for significant differences. Distances from clustered patients' locations to the nearest eye surgical facility ere calculated using Google Maps and analyses performed to identify if a relationship exists between distances travelled and the CSC for the area. Results: The prevalence of bilateral cataract blindness for males was 0.4% (n=8; 95% CI=0.1-0.7) and females 0.5% (n=17; 95% CI=0.3-0.8) and the CSC for males and females were 69.2% and 68.5% respectively. The difference in CSC was not statistically significant. Females aged ≥70 years reported more barriers to cataract surgical services compared to men. At a VA <3/60 in the better eye, 1km increase in the distance to the nearest eye surgicalcentre was associated with a reduction in the CSC for the area of 4.8% (Linear regression: F (1,95) = 16.06, p = 0.0001, R-Squared = 0.1446, Adjusted R-Squared = 0.1356). Conclusions: Older women (≥70 years) were the most vulnerable to untreated cataract blindness in Rwanda and therefore special programs need to target them for cataract surgical services. Distance to surgical facilities with ophthalmologists is related to the cataract surgical coverage even in a small country like Rwanda.